Eksistensi Ilmu Pengetahuan Di Era Revolusi 4.0 - Rohma Kubro; Ahmad Satrio; Mulhatur Rofi’ah; Akhmad Faidlaani; Muhammad Reza (LP2M, 2020)
This study is literature study with descriptive qualitative research with library research. This research is intended to explain the existence of science in the industrial revolution era 4.0. In this literature study, the author uses various written sources such as book, journal, and documents that are relevant to the study in this study. This study focuses on science and its existence in the industrial revolution era. The study results show that the existence of science at this time is still very much needed and has increased significantly. This is because the development of technology based on science has spread and entered the joints of aspects of human life.